Kajian perbedaan Bahasa Indonesia dan Bahasa Jerman dalam Struktur dan Penggunaan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Indonesian and German have significant differences in structure and usage. These differences can be seen in morphology, syntax, and grammar, including word order, the use of nouns, verbs, and conjugation and declination systems. Indonesian, as an agglutinative language, has a simpler structure with no changes in word form based on time or case, while German applies a complex system of declination and conjugation. In addition, differences in language use, especially in formal and informal sentence patterns, reflect the characteristics of each culture. This study aims to comprehensively analyze the structural and functional differences between Indonesian and German and examine their impact on learning both languages. The results of this study are expected to provide insights for foreign language learners, academics, and language practitioners in understanding the dynamics of the two languages.